The application of graph theory teaching method in ideological and political education of discrete mathematics - Wu, Yanping; Lv, Fangfang; Li, Meng (Applied mathematics and nonlinear sciences, 2023)
In order to fully implement curriculum ideology and politics in the current education and teaching work, it is extremely necessary to integrate curriculum ideology and politics with “discrete mathematics”. This article discusses the simple possibilities of teaching “mathematical decision” combined ideological and political education and training, so “mathematical decision” can know the same practice as ideological and political education, mutual support and mutual support. Because mathematics is an easy subject for computer education, teachers should deeply explore ideological and political issues when defining mathematics subjects, guide them with ideological and political education content in the teaching process, and play in the main activities of the curriculum. Those. In this article, the author mainly talks about the problems of creating an ideological and political curriculum for teaching inequality and the problems in the teaching process, proposes the established educational standards for determining the content of mathematics education, and aims to develop a theoretical and political basis for determining the content of mathematics education. Provide mathematics education through a combination of online and offline methods to integrate ideological and political education with the teaching of other professional subjects.